A comparative study on the tensile properties and failure mechanism of 3D MWK composites at room and liquid nitrogen temperature. Issue 7 (14th November 2013) - Li, Dian‐Sen; Zhao, Chuang‐Qi; Jiang, Lei; Lu, Na; Chen, Li‐Ming; Jiang, Nan
<x xml:space="preserve">Abstract</x> The tensile experiments on the three‐dimensional (3D) multi‐axial warp knitted (MWK) composites with four types of fiber architecture were performed at room and liquid nitrogen temperatures (as low as −196°C). Macroscopic fracture morphology and SEM micrographs both are examined to understand the deformation and failure mechanism. The results showed that the tensile properties can be affected greatly by the fiber architecture and these decrease significantly with the increase of the fiber orientation angle at room and liquid nitrogen temperatures. Meanwhile, the tensile properties at liquid nitrogen temperature have improved significantly than that of those at room temperature. Moreover, the damage and failure patterns of composites vary with the test temperature. At liquid nitrogen temperature, more microcracks appear and the brittle failure feature becomes more obvious; however, the interfacial adhesion capacity is enhanced significantly. In addition, the fiber architecture has remarkable effect on the failure mechanism at room and liquid nitrogen temperatures. POLYM. COMPOS., 35:1294–1305, 2014. © 2013 Society of Plastics Engineers